Program Analysis of The Indonesian Industrial Chamber of Commerce (KADIN) and Rokan Hulu Regency Regent in Inreasing Enterpreneurial Interest - Syahputra, Alfa (Jurnal Indonesia Sosial Sains, 2023)
This study aims to analyze the program of the Indonesian Chamber of Commerce and Industry (KADIN) and regent Rokan Hulu Regency in increasing entrepreneurial interest. This research uses qualitative methods by conducting case studies on the KADIN program in Rokan Hulu Regency. Data was collected through interviews and documentation, then analyzed using descriptive techniques. The results showed that the KADIN and regent Rokan Hulu Regency programs have a role in increasing entrepreneurial interest in the Rokan Hulu community, especially through programs held, coaching, and marketing. However, there are still several obstacles in implementing this program such as lack of support from local governments and public understanding that KADIN must provide business capital. Therefore, more effective efforts are needed in the realization of the KADIN program in Rokan Hulu Regency to increase interest in entrepreneurship in the community